Who's hogging the bandwidth?: The consequences of revealing the invisible in the home - Chetty, Marshini; Banks, Richard; Harper, Richard; Regan, Tim; Sellen, Abigail; Gkantsidis, Christos; Karagiannis, Thomas; Key, Peter (Proceedings of CHI 2010, 2010)
As more technologies enter the home, householders are burdened with the task of digital housekeeping—managing and sharing digital resources like bandwidth. In response to this, we created a domestic tool for bandwidth management called Home Watcher. Our field trial of Home Watcher showed that when resource contention amongst different household members is made visible, people's understanding of bandwidth changes and household politics are revealed. In this paper, we describe the consequences of showing real time resource usage in a home, and how this varies depending on the social make up of the household.